Self-reported symptoms and health complaints associated with exposure to Ixodes ricinus-borne pathogens - Azagi, Tal; Harms, Margriet; Swart, Arno; Fonville, Manoj; Hoornstra, Dieuwertje; Mughini-Gras, Lapo; Hovius, Joppe W.; Sprong, Hein; van den Wijngaard, Cees (Parasites & vectors, 2022)
The impact of infections with tick-borne pathogens (TBPs) other than Borrelia burgdorferi (s.l.) and tick-borne encephalitis virus (TBEV) on public health in Europe remains unclear. Our goal is to evaluate whether the presence of these TBPs in ticks can be associated with self-reported health complaints. We enrolled individuals who were bitten by I. ricinus between 2012 and 2015 and collected their relevant demographic and clinical information using a self-administered online questionnaire. A total of 4163 I. ricinus ticks sent by the participants were subject to molecular analyses for detection of specific TBPs. Associations between the presence of TBPs in ticks and self-reported complaints and symptoms were evaluated by means of a stepwise approach using a generalized linear model (GLM). Of 17 self-reported complaints and symptoms significant in the univariate analyses, 3 had a highly significant association (P < 0.01) with at least one TBP in the multivariate analysis. Self-reported Lyme borreliosis was significantly associated (P < 0.001) with B. burgdorferi (s.l.) infection. Facial paralysis was associated (P < 0.01) with infection with B. miyamotoi, N. mikurensis and R. helvetica. Finally, a significant association (P < 0.001) was found between nocturnal sweating and A. phagocytophilum. We found associations between the presence of TBPs in ticks feeding on humans and self-reported symptoms. Due to the subjective nature of such reports and the fact that infection was determined in the ticks and not in the patient samples, further prospective studies utilizing diagnostic modalities should be performed before any clinical outcome can be causally linked to infection with TBPs.